Permeability Behavior and Wastewater Filtration Performance of Mullite Bonded Porous SiC Ceramic Membrane Prepared Using Coal Fly Ash as Sintering Additive. Issue 3 (3rd July 2021) - Das, Dulal; Kayal, Nijhuma; Innocentini, Murilo Daniel de Mello
Abstract : With SiC as starting powder, waste fly ash as sintering additive and metal oxide as catalyst, mullite bonded SiC ceramic membrane was prepared at 1000°C using the conventional solid-state reaction method. Permeability parameters in both air and water flow tests were obtained using laboratory made set-up and the pure water permeability was measured at variable transmembrane pressures. The membrane exhibited excellent pure water flux of 5261 L.m −2 .h −1 .bar −1 with open porosity of 44.7% and mean pore size of 3.7 μm. With this membrane a high oil removal efficiency of 91% was achieved from the kitchen wastewater having initial oil concentration of 1657 mg.L −1 . The method developed here is technologically benign and addressed prevention of environmental pollution by utilizing hazardous waste material for fabrication of porous SiC ceramic membrane at a reduced cost with good mechanical, permeability characteristics and wastewater filtration efficiency. Hence, the proposed method for SiC membranes has good sustainability and is scalable for oily wastewater treatment. GRAPHICAL ABSTRACT: UF0001